2018
DOI: 10.1016/j.it.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Roles of Antiself Antibodies during Infection

Abstract: Antiself antibodies are most commonly associated with autoimmune disorders, but a large body of evidence indicates that they are also present in numerous infectious diseases. These autoimmune antibodies appear transiently during infection with a number of viruses, bacteria, and parasites and in some cases have been associated with the development of autoimmune disorders that develop after infection has been cleared. Traditionally these infection-associated autoantibodies are considered an erroneous byproduct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 61 publications
0
51
3
Order By: Relevance
“…Recent evidence suggests that any infection can trigger immune dysregulation, loss of immune tolerance, and development of immune‐mediated disease in an individual patient with a genetic, epigenetic, or susceptible microenvironmental milieu at the time of infection . However, certain organisms may cause specific immune‐mediated diseases.…”
Section: Putative Trigger Factorsmentioning
confidence: 99%
“…Recent evidence suggests that any infection can trigger immune dysregulation, loss of immune tolerance, and development of immune‐mediated disease in an individual patient with a genetic, epigenetic, or susceptible microenvironmental milieu at the time of infection . However, certain organisms may cause specific immune‐mediated diseases.…”
Section: Putative Trigger Factorsmentioning
confidence: 99%
“…The mechanisms underlying the loss of uninfected erythrocytes are not clear yet, but malaria-induced anemia was recently related to autoimmune responses in patients [ 10 ]. Malaria, as other highly inflammatory infectious diseases, induces a strong autoimmune response characterized by the generation of anti-self antibodies with different specificities [ 11 13 ]. Studies in mice models of malaria showed that antibodies recognizing the lipid phosphatidylserine (PS) exposed on the surface of uninfected erythrocytes promote their clearance contributing to anemia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some pathogens have been reported to be associated with the pathogenesis of autoimmune disorders 16,17 . These infectious agents trigger autoimmune diseases via various The proposed mechanisms include molecular mimicry, which antibodies against bacterial antigens that are similar to the host 19 . For example, autoimmune diseases such as Crohn's disease, ulcerative colitis, and sarcoidosis are commonly found in Mycobacterium tuberculosis patients 20 .…”
Section: Discussionmentioning
confidence: 99%